Dopage, adolescents et performance - Zorzoli, M. (Revue Medicale de la Suesse Romande, 2003)
If doping is generally considered a phenomena of the sport's world, the use of substances to achieve a better performance is an attitude which is rapidly spreading out in our society. Doping behavior is defined as the consumption of a product in order to face or pass an obstacle and be more performant. Even among adolescents, the will to increase the efficiency in sport or to modify the body appearance, push some people to use any kind of products: nutritional supplements, doping agents (anabolic steroids, amphetamines, etc.), with all the associated risks dues to the doubtful origin of some of these substances, the way they are consumed or their side effects. It is important that the medical community, and those who are in contact with the adolescents, realize that this kind of behavior exists, so to face it in an adequately manner, the same way they deal with the problem of alcohol, tobacco or drugs.